2019
DOI: 10.1038/s41598-019-44480-0
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic male-specific sterilization system using the mammalian pro-apoptotic factor in a malaria vector mosquito

Abstract: Conditional cell death systems are useful for various aspects of basic science with a wide range of applications, including genetic pest control. We recently demonstrated that expression of the mammalian pro-apoptotic factor, B-cell leukaemia/lymphoma 2-associated X protein (Bax), can induce apoptosis in specific tissues by using tissue specific promoters in silkworm and mosquito. Here, we newly identified a functional promoter in the Asian malaria vector, Anopheles stephensi , which ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…We examined endogenous transcript accumulation profiles for each of these genes in both male and female reproductive tissues of A. stephensi to evaluate whether their promoters might be of potential future interest for driving germline-restricted expression of Cas9. We used the previously described A. stephensi male-specific β 2 -tubulin gene ( Yamamoto et al 2019 ), expressed in meiotic cells of the testes, as a control of late meiotic expression and technique ( Figure 4 ). We first confirmed that β 2 -tubulin transcription is indeed male-specific using quantitative gene amplification (qPCR; Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We examined endogenous transcript accumulation profiles for each of these genes in both male and female reproductive tissues of A. stephensi to evaluate whether their promoters might be of potential future interest for driving germline-restricted expression of Cas9. We used the previously described A. stephensi male-specific β 2 -tubulin gene ( Yamamoto et al 2019 ), expressed in meiotic cells of the testes, as a control of late meiotic expression and technique ( Figure 4 ). We first confirmed that β 2 -tubulin transcription is indeed male-specific using quantitative gene amplification (qPCR; Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Anopheles stephensi SDA500 strain, was maintained in 26˚C, 60-80% relative humidity, and a 13-h/11-h light/dark cycle at Jichi Medical University [13]. Adults were fed on a filter paper soaked with 5% fructose (Nacalai Tesques, Kyoto, Japan).…”
Section: Animalsmentioning
confidence: 99%
“…Developing sterilization methods that specifically target fertility genes may provide an alternative avenue to produce males that are fit for mating. Multiple, more precise, transgenic sterilization systems have been developed in some mosquito vectors, including those which preserve male fertility but kill offspring in post-embryonic developmental stages 19 22 , those which express pro-apoptotic factors in the testes 23 , and those which combine male sterilization and female-killing 24 . While these systems cause transient species-specific population suppression following release, none have yet been adopted in the most important African malaria vector Anopheles gambiae .…”
Section: Introductionmentioning
confidence: 99%